2015
DOI: 10.1080/15659801.2016.1176689
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter affects the survival and predation rates for large and small Pinus seeds in the Qinling Mountains, China

Abstract: It is generally accepted that leaf litter covers seeds, which may be beneficial for their survival, but it is unclear whether leaf litter contributes in different ways to the survival of plant seeds with contrasting sizes. In this study, we examined the effect of different levels of leaf litter coverage on seed predation and foraging/caching for small-seeded Pinus tabulaeformis and large-seeded Pinus armandii in the Qinling Mountains, China. Our results showed that leaf litter failed to protect P. armandii see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Seed transport by rodents not only helps disperse seeds and avoid parental competition (Nathan and Muller-Landau, 2000;Jansen et al, 2014), but also increases the chances that seeds reach a suitable location to germinate (Steele et al, 2014;Wang and Corlett, 2017). Seed removal by rodents is complex and varies with respect to seed size and abundance (Batisteli et al, 2020;Dylewski et al, 2020;Kuprewicz and García-Robledo, 2019;Pardini et al, 2017), seed chemical defenses (Shimada et al, 2015;Zhang et al, 2013), leaf litter (Yu et al, 2016), and location (Steele et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed transport by rodents not only helps disperse seeds and avoid parental competition (Nathan and Muller-Landau, 2000;Jansen et al, 2014), but also increases the chances that seeds reach a suitable location to germinate (Steele et al, 2014;Wang and Corlett, 2017). Seed removal by rodents is complex and varies with respect to seed size and abundance (Batisteli et al, 2020;Dylewski et al, 2020;Kuprewicz and García-Robledo, 2019;Pardini et al, 2017), seed chemical defenses (Shimada et al, 2015;Zhang et al, 2013), leaf litter (Yu et al, 2016), and location (Steele et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf litter cover might increase rodent search time (and thus energy expenditure), thereby decreasing the chances of finding the seeds (Sotes et al, 2018;Zhao et al, 2014). However, leaf litter cover may only increase the seed survival time but not the survival rate (Yan et al, 2011;Yu et al, 2016). For exemple, seed survival of Quercus wutaishanica was independent of leaf cover, and all seeds were removed or consumed by rodents after 14 d (Yan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that factors like leaf litter, seed density and tree cover may affect the removal of these dispersed seeds and therefore species recruitment (Forget, 1992;Forget, 1993;Myster & Pickett, 1993;Bustamante & Vásquez, 1995;Cintra, 1997;Dalling, 2002, Yu et al, 2015Dudenhöffer et al, 2016). For example, Janzen (1970) and Connell (1971) suggested that density dependent seed removers prefers areas with high seed densities becoming this areas in less safe to the species regeneration.…”
Section: Introductionmentioning
confidence: 99%